The larval and imaginal oenocytes of Callosobruchus maculatus (Fabricius) (Coleoptera: Bruchidae). - Pajni, H. R. (Contributions to Entomology = Beiträge zur Entomologie, 1968)
There are two generations of oenocytes in Callo8obruchus maculatus (Fabricius), the large larval oenocytes and comparatively small imaginal oenocytes, both scattered haphazardly in the fat body but elustered particularly elose to and in between the stigmata. The larval oenocytes are lost during the pupal stage and are replaced by imaginal oenocytes arising from segmental groups of hypodermal cells which make their appearance in the vicinity of spiracles in the prepupa. The structure, origin and metamorphic behaviour of the oenocytes are discussed.